Proceso de atención de enfermería en lactante menor con síndrome de acondroplasia. - Jimenes Cuichan, Mercedes Rocío (2022)
Achondroplasia syndrome in one of the most common diseases of dwarfism, is a bone genetic disorder that causes a number of symptoms that prevent the normal and healthy growth of the child. In the present clinical case, it is of a 6-month-old male pediatric patient diagnosed with achondroplasia syndrome since the mother's pregnancy, who is regularly treated at the Martin Icaza Hospital. In the present clinical case, the nursing care process was applied by applying the NANDA, NOC, NIC taxonomies, to provide the necessary nursing care for a prompt recovery of the patient.